A Cowrie's Life: The São Bento and Transoceanic Trade in the Sixteenth Century. Issue 4 (1st October 2020) - Wintjes, Justine
ABSTRACT: A collection of money cowries ( Monetaria moneta ) was discovered in the early 1980s inside a bronze cannon salvaged from the wreck site of the São Bento (1554), at the mouth of the Mzikaba River, Eastern Cape, South Africa. Using an approach inspired by 'object biography', I consider the presence of these cowries in a museum, their possible Maldivian origin, their interrupted West African future and their wider social, economic and ecological entanglements as a global trade item circulating in a pre-industrial world. This exploration sheds some light on the slave trade linking the Indian Ocean and Atlantic in the sixteenth century and the intertwined itineraries of cowries and slaves.